Applied Social Sciences : Economics and Politics. - Runcan, Patricia-Luciana (Cambridge Scholars Publishing, 2013)
This book, Applied Social Sciences: Economics and Politics, is a collection of quantitative and qualitative studies carried out in the field of economic and political sciences useful in the social sphere. Theoretical essays and empiric research attempt to explain some difficult economic and political phenomena such as need scale and true productivity, audit of financial statements, evaluation of students' action on the labour market, the financing and quality of public higher education, resis ...